2020
DOI: 10.3390/brainsci10090627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brain Lesions on Voluntary Cough in Patients with Supratentorial Stroke: An Observational Study

Abstract: Patients with stroke are known to manifest a decreased cough force, which is associated with an increased risk of aspiration. Specific brain lesions have been linked to impaired reflexive coughing. However, few studies have investigated whether specific stroke lesions are associated with impaired voluntary cough. Here, we studied the effects of stroke lesions on voluntary cough using voxel-based lesion-symptom mapping (VLSM). In this retrospective cross-sectional study, the peak cough flow was measured in pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
(98 reference statements)
1
11
0
Order By: Relevance
“…To ensure that the patient had a full understanding, a pre-assessment education and practice were allowed. Moreover, Lee et al reported that statistical correlation between the PCF and MMSE, the levels were only modest [42]. These modest levels of correlation were in parallel to our results.…”
Section: Discussionsupporting
confidence: 91%
“…To ensure that the patient had a full understanding, a pre-assessment education and practice were allowed. Moreover, Lee et al reported that statistical correlation between the PCF and MMSE, the levels were only modest [42]. These modest levels of correlation were in parallel to our results.…”
Section: Discussionsupporting
confidence: 91%
“…33,34 Increased severity of dysphagia increases the risk of aspiration pneumonia. 35 Neurological problems such as seizure can predispose a patient to acquire post-stroke aspiration pneumonia. 36 Patients with ischemic stroke are less likely to develop aspiration pneumonia compared with patients with a hemorrhagic type of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Reflexive coughs are produced by brainstem networks. [2,7] Voluntary coughing is achieved by controlling the respiratory muscles via the cerebral cortex. [7,8] Patients with ischemic stroke have been reported to experience weakness of the respiratory muscles, including the diaphragm, and a decrease in peak cough flow (PCF) during voluntary coughing.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Patients with ischemic stroke who develop respiratory complications may experience difficulty swallowing, impaired cough reflex, and poor excretion, increasing the risk of aspiration. [2] Decreased voluntary cough function reduces the ability to clear mucus or secretions from the airways and increases the risk of aspiration pneumonia. [3,4] Coughing and swallowing both share similar nerves and laryngeal and respiratory muscles.…”
Section: Introductionmentioning
confidence: 99%